ANALYSIS OF THE INFLUENCE OF FINANCIAL RATIO ON VALUE OF MANUFACTURING COMPANIES - Jordan Adam Simanjuntak; Mas Intan Purba (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
A company is an organization consisting of 2 or more people whose goal is to create a product for profit. A company listed on the IDX is a company that has shares that can be purchased by the general public. Basically, a company listed on the IDX must be a company that have large capital. what determines investors will invest their capital in the company is the company's financial performance. investors will make decisions to invest some capital in the company through the company's financial performance. This study aims to determine the effect of CR, DER, TATO, ROA, on the PBV Ratio manufacturing companies in the pharmaceutical sub-sector industry listed on the IDX in 2016-2019 This research approach uses a quantitative approach and uses a purposive sampling technique, 11 samples of manufacturing companies in the pharmaceutical sub-sector industry listed on the IDX in 2016-2019. used is secondary data. Secondary data is the financial statements of manufacturing companies in the pharmaceutical sub-sector industry listed on the Indonesia Stock Exchange in 2016-2019 on the web www.idx.co.id. The result is that CR, DER, TATO, ROA have a simultaneous influence on the PBV Ratio of manufacturing companies in the pharmaceutical sub-sector industry listed on the IDX in 2016-2019. manufacturing companies in the pharmaceutical sub-sector industry listed on the IDX in 2016-2019